A 240-GHz circularly polarized FMCW radar based on a SiGe transceiver with a lens-coupled on-chip antenna. Issue 3 (13th March 2015) - Statnikov, K.; Grzyb, J.; Sarmah, N.; Malz, S.; Heinemann, B.; Pfeiffer, U. R.
Abstract : A 240-GHz monostatic circular polarized SiGe frequency-modulated continuous wave radar system based on a transceiver chip with a single on-chip antenna is presented. The radar transceiver front-end is implemented in a low-cost 0.13 µm SiGe HBT technology version with cut-off frequencies fT /fmax of 300/450 GHz. The transmit block comprises a wideband ×16 frequency multiplier chain, a three-stage PA, while the receive block consists of a low-noise amplifier, a fundamental quadrature down-conversion mixer, and a three-stage PA to drive the mixer. A differential branch-line coupler and a differential dual-polarized on-chip antenna are added on-chip to realize a fully integrated radar transceiver. All building blocks are implemented fully differential. The use of a single antenna in the circular polarized radar transceiver leads to compact size and high sensitivity. The measured peak-radiated power from the Si-lens equipped radar module is +11 dBm (equivalent isotropically radiated power) at 246 GHz and noise figure is 21 dB. The characterization bandwidth of the radar transceiver is 60 GHz around the center frequency of 240 GHz, and the simulated Tx-to-Rx leakage is below −20 dB from 230 to 260 GHz. After system calibration the resolution of the system to distinguish between two targets at different distance of 3.65 mm is achieved, which is only 21% above the theoretical limit.